How the Color of a Classroom Influences Learning Outcomes in 3rd Grade Primary Education: A Comparative Study in a Private Subsidized School in Santiago, Chile - Vidal-Rojas, R (UNIV COSTA RICA, EDITORIAL, 2020)
Conditions related to how habitable classrooms were at a school in the commune of La Florida, Chile were analyzed and assessed. The purpose of the study is to measure how color and lighting impacts the performance of 3rd grade primary school students a Their minimal changes were made to classrooms. The study design was partially cross-sectional and correlational which facilitated collection of academic performance data to be collected so as to better understand the causal relationship between classroom color and learning. A prototype technique was used through which an actual classroom was remodeled and the results measured in two manners. Results were compared among students in the Math and Language class, before and a Ther the classroom was remodeled. The same results of the students were compared in the remodeled classroom with students at the same grade level in a conventional classroom. The study revealed that an appropriate and focused complementary color combinations in the classroom help stimulate and improve student learning, in disadvantageous conditions where conventional classrooms cannot afford significant remodeling. Overall improvement in student learning requires classroom environments that incorporate elements to make classrooms more conducive to learning.